Greenwashing practices in the asset management market: a detailed ESG analysis on equity funds - Fillippi, Paola Bahdur (2022)
The number of initiatives and efforts aimed at building a more sustainable future has greatly increased in recent years. However, what was supposed to be aimed at mitigating the effects of climate change is actually just an effort by agents to be part of a billion-dollar market that grows every year. Thus, it is possible to increasingly observe the growth of cases of greenwashing, leading to a sustainability that is actually symbolic. Bearing in mind that major societal problems require changes at various levels and systems, this study focuses on presenting factors that contribute to greenwashing practices and to expand the literature in this regard based on evidence and concrete examples from the analysis of a database of European funds that call themselves sustainable. In order to do that, a qualitative analysis is conducted using the public communication of 182 European funds which promote themselves as sustainable. After analyzing the results it was possible to identify factors from different levels that contribute to a misleading communication such as the use of confusing methodologies of the very tools that should help the investor, methodological differences to define sustainable investment by the firms, agendas with unrealistic and overly positive targets, non-standardization of sustainability-related activity reports and lack of auditing.